How Do Parental Factors Increase the Probability for Autism and Attention Deficit Hyperactivity Disorder? - Shumoos Riadh M.Shafeea; Zinah M. Anwer; Zainab Ali Saleem (College of Pharmacy University of Baghdad, 2023)
Two prevalent neurodevelopment disorders in children are attention deficit hyperactivity disorder (ADHD) and autism spectrum disorder (ASD). The fifth version of the Diagnostic and Statistical Manual of Mental Disorders describes autism as a condition marked by limitations in social communication as well as restricted, repetitive behavior patterns. While impulsivity, hyperactivity, and lack of concentration are signs of attention deficit hyperactivity disorder. Boys experience it more frequently than girls do. This study sought for possible factors that put children at risk for autism and attention deficit hyperactivity disorder, and it investigated the association between neurodevelopment disorders in children and parental risk factor in Iraqi population. This was a cross sectional, comparative study applied in The National Center for Autism/Medical City Complex from January to April 2022.In which120 child withneuro development disorders and 120 controls participated. The data collected from the questionnaires was analyzed using SPSS 25. Independent T-test and Chi-Square test were carried out for the bivariate analysis of the data. Among the tested variables four parent-related factors were significantly (P-value < 0.05) associated with neurodevelopment disorders in children: Family history of psychiatric illness, smoking of any parent, pregnancy and labor complications, used progesterone during pregnancy. In addition to these significant parent-related risk factors, paternal age at conception time were significantly (P-value < 0.05) associated with neurodevelopment disorders of children. Based on this case control study, mothers with pregnancy & labor complications, paternal age at conception, smoking of any parent,mothers used progesterone during pregnancy and family history of psychiatric illness, had higher risk of neurodevelopment disorders.